Amplification of light collection in solid-state dye-sensitized solar cells via the antenna effect through supramolecular assembly1. Issue 15 (21st April 2015) - Louahem M'Sabah, Bilel; Boucharef, Mourad; Warnan, Julien; Pellegrin, Yann; Blart, Errol; Lucas, Bruno; Odobel, Fabrice; Bouclé, Johann
<x xml:space="preserve">Abstract</x> Efficient energy transfer steps from an organic antenna bound via supramolecular interactions to an organic dyad are demonstrated within solid-state dye-sensitized solar cells.